Inheritance in the Join Calculus (extended abstract) - Fournet, Cédric; Laneve, Cosimo; Maranget, Luc; Remy, Didier (Foundations of Software Technology and Theoretical Computer Science, 2000)
We propose an object-oriented calculus with internal concurrency and class-based inheritance that is built upon the join calculus. Method calls, locks, and states are handled in a uniform manner, using asynchronous messages. Classes are partial message definitions that can be combined and transformed. We design operators for behavioral and synchronization inheritance. Our model is compatible with the JoCaml implementation of the join calculus.